Morphology Characteristics of Local Rice (Oryza Sativa L.) Rice Lands of Long Tebulo Village, North Kalimantan - Hariyati, Tati; Putra, Marlan Usmani; Zakaria, Zakaria (Journal of Agriculture, 2024)
Local rice (Oriza sativa L). is an annual plant cultivated by local people once a year. Local rice in the Malinau Regency area has different names for rice cultivars based on the local community's ethnicity or the person who brought the seeds. The aim of this research is to find out the local rice cultivars in the rice fields in Long Tebulo village and to find out the characteristics of the local rice fields in Long Tebulo village. This research was carried out from November 2020 to February 2021. The methods used in the research were qualitative analysis, exploration and characterization. The research results are available. There are 10 types of local rice cultivars, there are 6 sticky rice cultivars including Adan Saleng, Adan Bala, Adan Pute, Uro, Pulut Embeng, Pulut Bu'ung, and 4 ordinary rice cultivars, namely Bere, Bawang, and Gula/bread, based on plant characteristics. Rice has different ages. plant height, panicle length, grain shape, age, and rice color.